PROCESS FOR CHROMIUM (VI) REMOVAL FROM MECHANIZED TANNERY WASTEWATER USING ACTIVATED CARBON OBTAINED FROM TANNERY SOLID WASTES (FUDMA JOURNAL OF SCIENCES, 2021)
This study offers an integrated process for treatment and recycling of tannery waste, it has a dual purpose. First the activated carbon has been prepared from leather shaving and buffing dust by physical activation. Both the raw material (leather waste) and the prepared activated carbon were analyzed by DTG, Thermo Gravimetric Analysis TGA, and scanning electron microscope. The adsorption tests of methylene blue and iodine onto the raw material and the prepared adsorbent were carried out and it was found that the adsorption capacity of the activated carbon was enhanced by the physical activation. The Activated Carbon was then characterized by equation of Brunauer-Emmett-Teller surface area and Fourier transforms infrared spectroscopy (FTIR). The Brunauer-Emmett-Teller surface area was found to be 491.05 and 242.60 m2/g for activated carbons prepared from Leather Savings and Buffing Dust respectively and the functional groups on the adsorbent surface were mainly CN, NH, OH, CO and CS. Secondly, the performance of the prepared activated carbon was assessed by adsorption of chromium (VI) from a synthetic solution, and then the chromium (III) present in the tanning effluent. The results revealed a decrease of chromium by 76% and 73% for the activated carbons prepared from Leather Savings and Buffing Dust, respectively
Keywords: Leather Shaving, Buffing dust, Tannery effluent, Activated Carbon, Adsorption and Chrome ion